Rethinking friendship : hidden solidarities today (PRINCETON UNIV Press, 2006)
"Rethinking Friendship not only describes the varied nature of personal relationships today, but also locates friendship in contemporary debates about individualization and the supposed "collapse of community." Exploring friendships with partners and family as well as "friends," the book reveals ways in which friends and friendlike ties are an important and unacknowledged source of social glue." "Combining scholarly depth and rich description, this book will appeal to all those interested in informal social relationships, including students of methodology and policymakers."--Jacket.